Edukasi Masyarakat melalui Siaran Ceramah RRI Takengon: Puasa sebagai Latihan Kesabaran Menghadapi Ujian - Ansor; Farid Fauzi; Marlina (Lembaga Yasin AlSys, 2026)
Fasting serves not only as a ritual act of worship but also as a means of cultivating patience, self-control, and spiritual resilience in facing various trials in life. This community service activity aims to enhance public understanding of fasting as a means of cultivating patience and spiritual resilience through religious lecture broadcasts on RRI Takengon. The activity was conducted using an educational and communicative approach through live lectures based on the Qur’an, hadith, and phenomena in community life. The activity comprised the preparation, broadcasting, and evaluation stages, using listener participation and feedback as indicators of success. The results showed that radio broadcasts were effective in enhancing public understanding of the meaning of fasting as a means of self-control, emotional management, and strengthened resilience in facing various life challenges. Listener enthusiasm during interactive sessions via telephone and WhatsApp demonstrated the community’s strong need for contextual religious education. Collaboration between the higher education institution and RRI Takengon also strengthened the function of public broadcasting media as a means of da’wah, education, and community empowerment. This activity confirms that radio broadcasting can serve as an innovative and applicable community service model for expanding religious literacy and building community spiritual resilience.